Phase Composition and Microstructure of Cast Al-6%Mg-2%Ca-2%Zn Alloy with Fe and Si Additions - Vitali Doroshenko; Pavel Shurkin; Tatyana Sviridova; Anastasiya Fortuna; Ivan Shkaley (Metals, 2023)
Investigating the effect of Fe and Si is essential for any new Al-based composition, as these impurities can be easily found both after primary production and recycling. This study is dedicated to filling the gap in revealing the phase composition of an Al-6%Mg-2%Ca-2%Zn alloy after the combined and separate addition of Fe and Si. This was addressed by permanent mold casting and solid solution heat treatment. The investigation of slowly solidified samples also contributed to understanding potential phase transitions. It was found that the alloy containing 0.5%Fe can have nearly spherical intermetallics after heat treatment, whereas a higher Fe content brought the formation of a needle-shaped Al3Fe intermetallic. We explain this by the formation of a ternary α-Al + Al10CaFe2 + Al4Ca eutectic, which is more compact in as-cast condition compared to divorced binary α-Al + Al4Ca and α-Al + Al3Fe eutectics. Similarly, 0.5%Si readily incurred the formation of a needle-shaped Al2CaSi2 intermetallic, probably also by a binary reaction L → α-Al + Al2CaSi2. In the solidified samples, no Mg2Si phase was found, even in slowly solidified samples. This is contrary to the thermodynamic calculation, which suggests a peritectic reaction L + Al2CaSi2 Mg2Si. Interestingly, the addition of 0.5%Si caused an even coarser microstructure compared to the addition of 1%Fe, which caused the appearance of a primary Al3Fe phase. We conclude that the new alloy is more tolerable to Fe rather than Si. Specifically, the addition of 0.5%Fe can be added while maintaining a fine morphology of the eutectic network. It was suggested that the morphology of eutectic and solid solution hardening governed the mechanical properties. The strength of the alloys containing separate 0.5%Fe (UTS = 215 ± 8 MPa and YS 146 ± 4 = MPa) and the combined 0.5%Fe and 0.5%Si additions (UTS = 195 ± 14 MPa and YS ± 1 = 139 MPa) was not compromised compared to the alloy containing 0.5%Si (UTS 201 ± 24 = MPa and YS = 131 ± 1 MPa).